Formação política e resistência: uma experiência contra-hegemônica na Prelazia de São Félix do Araguaia - Paganini, Vera Lúcia Alves Mendes (2018)
This thesis, inserted in the area of Education, is linked to the Research: Education, Work and Social Movements, of the Postgraduate Program in Education, School of Education, Federal University of Goiás. It is a study of specific historical realities, in the religious territory called the Prelature of São Félix do Araguaia-MT, beginning in the 1970s. The problem that arises as a focus of the research is: in what way did the formative processes contribute to the spread of the Gospel and what was the role of the Church in the political and educational formation that has developed there since then? The delimitation of the subject is the analysis of the elements that facilitated the appearance of intellectuals who worked in the construction of a counter-hegemony, becoming social protagonists, implicated in the conflicts over land rights between squatters, Indians, peasants, and the small as well as large landowners. The objective is to understand the educational and formative processes experienced by the communities of the Prelature and the role of the political-collective subject in the formation of the organic intellectual; how he was formed and was constituted in the space of formation in which the construction and reconstruction of the counter-hegemonic project took place. The emphasis is on the resources for building and reconstructing identities and powers; which leads us to the study of memories and identities to understand the formation of an intellectual from the place where one builds and moves. In the investigation of the subjects we seek theoretical contributions on memory with Thompson, Halbwachs and Aróstegui for the relevance of the reports in the revisiting of time and events, and for the importance of collective memory in the constitution of history. To categorize the autobiographical accounts, we work with Bolivar, Domingo y Fernández and Bourdieu, observing their subjective dimension. The reflection on school education is supported by Freire and the study of the organic intellectual is based on Gramsci. The reports evoke metaphors and images fundamental in the interpretation of the facts, which we have studied with Bakhtin, to understand the exhortative religious discourse and the imagistic constructions, close to the literary language. The result of the analysis indicates that the political-social process developed there was marked by the condition of the place and the identity of the protagonists. The squatters, the southern settlers, the Catholic Church, the landowners and the state are identified as protagonists. Education, evangelization and resistance are categories of analysis of the object of study. Two movements stand out: one marked by the construction of power relations that are closer to the interests and needs of unfavorably positioned social groups, which enhances the production of values, meanings and formal learning and knowledge. Another one of maintenance of the relations of power by the executive bureaucracy of the State, by the capitalist order and by the logic of technical rationality. Resulting from different texts and contexts, the collective subject is formed in the contradictions of one's own limitations, from which emerge the organic intellectuals who undertake the counter-hegemonic project emerge whose bases, for a period, confront the project already consolidated by the system of the federal government. There are changes of political fronts that, in the disputes, lead education projects both on the side of the government and on the side of the Prelature, giving a particular focus to party politics in the contexts of that territory. Our study was thought of moving from local to global and through different arenas of action. The emphasis then, is on the action of the organic intellectual as a political and social force of the region, whose resistance lies in the contradictions and continuance of the two blocs, alternating the local governments, responsible for the social and political events that permeate the relations until the present time.